#### Answer

LCD=(2)(3)(x+1)(x+1)=6$(x+1)^{2}$

#### Work Step by Step

$\frac{1}{3x+3}$, $\frac{8}{2x^{2}+4x+2}$
2$x^{2}$+4x+2=2$x^{2}$+2x+2x+2=2x(x+1)+2(x+1)=
=(2x+2)(x+1)=2(x+1)(x+1)
3x+3=3(x+1)
LCD=(2)(3)(x+1)(x+1)=6$(x+1)^{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

LCD=(2)(3)(x+1)(x+1)=6$(x+1)^{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.